PEMANFAATAN FITUR BREAKOUT ROOM ZOOM UNTUK MENDUKUNG MODEL PEMBELAJARAN KOOPERATIF DI MASA PANDEMI COVID-19 - Suci Yuniarti; Tri Hariyati Nur Indah Sari (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2021)
The online learning policy during the COVID-19 pandemic presents its challenges in implementing the cooperative learning model in schools. This study describes the use of the breakout room zoom feature in the cooperative learning model, especially Student Facilitator and Explaining (SFE) and the Number Head Together (NHT) types. This research is a qualitative descriptive study. The data sources of this research are two students who carry out teaching practice in schools. Data were collected using observation and documentation. The results of data analysis show that the implementation of the SFE and NHT cooperative learning models by utilizing the breakout room feature is very good. In addition, the effectiveness of the SFE and NHT cooperative learning models by utilizing the breakout room feature is included in the very effective and effective criteria.